Editorial - Li, Xingwang; Xu, Lingwei; Wang, Han (Journal of Mobile Multimedia, 2023)
In today’s rapidly evolving technological landscape, the intersection of healthcare with innovative technologies has given rise to a complete shift in the way we perceive and access medical services. The advent of Intelligent Contactless Sensors and Micro Processing Systems provides a significant leap forward to propel the development of Smart mHealth Systems that promise to revolutionize healthcare delivery, monitoring and management. Moreover, these advancements hold the potential to bridge the gap between traditional medical practices and modern digital solutions to enhance patient care and to promote preventative measures in personal well-being. This special issue has discussed about the multifaceted dimensions of Intelligent Contactless Sensors and Micro Processing Systems in the context of Smart mHealth Systems. It also explores their fundamental principles, technological underpinnings and transformative applications across various domains of healthcare. From wearable devices that monitor vital signs without physical contact to miniature processing units that analyze data in real-time, the possi- bilities are boundless. Overall, four papers were accepted in this special issue after rigorous selection process. The compilation of these accepted papers is presented in this editorial showcase with each shedding light on the conver- gence of these technologies and their profound impact on patient-centric care, remote monitoring, disease management, and health promotion.